“Sekolah Penggerak” and Centers of Excellence - Rotty, Viktory NJ; Kainde, Quido; Pitoy, Jureyke I.; Punuh, Liesje Grace Lourino (JR Education, 2022)
School programme mover is effort for realize vision education in Indonesia and aims for develop participant teach Pancasila for realizing an advanced Indonesia with character independent, independent and character. this program focuses on development results comprehensive learning, include skill and character students, started with source power quality human (head schools and teachers). School Program mover is improvement of the transformation program school before. School Program mover will accelerate public / private schools all over the world condition school for move 1-2 steps more forward. Program done gradual and integrated with ecosystem until whole schools in Indonesia into the School Program Activator. School Program mover have destination for motivate the change process in the unit education so that achievements results study participant educate could experience enhancement in a manner thorough, deep aspect knowledge nor character. This program to use realize Profile Pancasila students.